Evaluation of Additively-Manufactured Internal Geometrical Features Using X-ray-Computed Tomography - Baumgärtner, Benjamin; Rothfelder, Richard; Greiner, Sandra; Breuning, Christoph; Renner, Jakob; Schmidt, Michael; Drummer, Dietmar; Körner, Carolin; Markl, Matthias; Hausotte, Tino (Journal of Manufacturing and Materials Processing, 2023)
X-ray-computed tomography (CT) is today’s gold standard for the non-destructive evaluation of internal component defects such as cracks and porosity. Using automated standardized evaluation algorithms, an analysis can be performed without knowledge of the shape, location, or size of the defects. Both the measurement and the evaluation are based on the fact that the component has no internal structures or cavities. However, additive manufacturing (AM) and hybrid subtractive procedures offer the possibility of integrating internal structures directly during the building process. The examination of powder bed fusion (PBF) samples made of Ti64 and PA12 showed that the standardized evaluation methods were not able to identify internal structures correctly. Different evaluation methods for the CT-measured values were analyzed and recommendations on a procedure for measuring internal structures are given. <
Keywords: computed tomography; additive manufacturing; internal geometrical feature; Ti64; PA12